2009
DOI: 10.1200/jco.2008.20.1566
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients With Early-Stage Breast Cancer Treated With Doxorubicin-Based Adjuvant Chemotherapy As a Function of HER2 and TOP2A Status

Abstract: A B S T R A C T PurposeAmplification and deletion of the TOP2A gene have been reported as positive predictive markers of response to anthracycline-based therapy. We determined the status of the HER2 and TOP2A genes in a large cohort of breast cancer patients treated with adjuvant doxorubicin (A) and cyclophosphamide (C). Patients and Methods TOP2A/CEP17and HER2/CEP17 fluorescent in situ hybridization (FISH) were performed on tissue microarrays (TMAs) constructed from 2,123 of the 3,125 women with moderate-risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 33 publications
5
41
1
Order By: Relevance
“…The prognostic and predictive value of measuring ERBB2 and TOP2A expression has long been a matter of debate (39)(40)(41)(42)(43)(44)(45)(46). To our knowledge, however, a systematic study of ERBB2 and TOP2A in the same cohorts investigating the correlation of DNA amplification, gene and protein expression, and analyzing their prognostic relevance has so far not been published.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic and predictive value of measuring ERBB2 and TOP2A expression has long been a matter of debate (39)(40)(41)(42)(43)(44)(45)(46). To our knowledge, however, a systematic study of ERBB2 and TOP2A in the same cohorts investigating the correlation of DNA amplification, gene and protein expression, and analyzing their prognostic relevance has so far not been published.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between TOP2A gene status/topo2a protein expression and response to anthracyclines has been addressed by a legion of studies [23,26,30,[35][36][37][38][39][40][41][42][43][44][45][46][47] and are currently a matter of considerable debate. Most studies were essentially retrospective, and included breast cancer patients treated with anthracycline combinations rather than single agent anthracycline and, therefore, the activity of the other drugs of the combination could obscure any existing relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to ER, the HER2 status of BC narrows the pool of candidates eligible for HER2-directed therapies, but it does not definitively select those who will respond. Several studies have reported that HER2 may be a predictive marker of response to anthracycline-based chemotherapy [98][99][100][101]. It has also been suggested that HER2 positivity is predictive of better response to higher dose anthracycline-containing regimens compared with standard regimens [102,103] and to taxane compared with non-taxane-containing regimens [104,105], however, the predictive value of HER2 remains a complex subject and further validation is still required [98].…”
Section: Her2mentioning
confidence: 99%